2014
DOI: 10.1111/tpj.12538
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor WRKY46 regulates osmotic stress responses and stomatal movement independently in Arabidopsis

Abstract: SUMMARYDrought and salt stress severely inhibit plant growth and development; however, the regulatory mechanisms of plants in response to these stresses are not fully understood. Here we report that the expression of a WRKY transcription factor WRKY46 is rapidly induced by drought, salt and oxidative stresses. T-DNA insertion of WRKY46 leads to more sensitivity to drought and salt stress, whereas overexpression of WRKY46 (OV46) results in hypersensitivity in soil-grown plants, with a higher water loss rate, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
139
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 71 publications
(98 reference statements)
9
139
0
Order By: Relevance
“…In most cases, starch content in guard cells has been estimated on a relative value scale by comparing the intensity of iodine-stained guard cell chloroplasts (Tallman and Zeiger, 1988;Kang et al, 2007;Valerio et al, 2011;Prasch et al, 2015). In a few studies, starch content was determined quantitatively using the oil-well technique on freeze-dried leaflets Ding et al, 2014) or spectrophotometrically using guard cell-enriched epidermal fragments (Daloso et al, 2015), but, in these cases, no temporal dynamics were reported. Thus, our knowledge of starch metabolism in guard cells has remained fragmentary, mostly correlative in nature, and even contradictory.…”
Section: Carbon Sources For Guard Cell Starchmentioning
confidence: 99%
“…In most cases, starch content in guard cells has been estimated on a relative value scale by comparing the intensity of iodine-stained guard cell chloroplasts (Tallman and Zeiger, 1988;Kang et al, 2007;Valerio et al, 2011;Prasch et al, 2015). In a few studies, starch content was determined quantitatively using the oil-well technique on freeze-dried leaflets Ding et al, 2014) or spectrophotometrically using guard cell-enriched epidermal fragments (Daloso et al, 2015), but, in these cases, no temporal dynamics were reported. Thus, our knowledge of starch metabolism in guard cells has remained fragmentary, mostly correlative in nature, and even contradictory.…”
Section: Carbon Sources For Guard Cell Starchmentioning
confidence: 99%
“…Second, both WRKY46 and VITL1 are expressed in root stele as well as in vasculature tissues in shoots ( Fig. 2; Gollhofer et al, 2011;Ding et al, 2014), suggesting they have similar expression patterns. Third, down-regulation of VITL1 significantly increases Fe concentrations in xylem sap of wrky46 mutants and thus restores Fe homeostasis and Fe deficiency response of wrky46 mutants to that of the wild type (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our microarray data revealed that the expression of two Fe translocation-related genes, NIC-OTIANAMINE SYNTHASE2 (NAS2) and VACUOLAR IRON TRANSPORTER1-LIKE1 (VITL1), was affected by WRKY46 overexpression (Ding et al, 2014). NAS2 encodes an enzyme that synthesizes nicotianamine and is responsible for Fe transport inside the body of plants (Schuler et al, 2012).…”
Section: Wrky46 Regulates Expression Of the Genes Involved In Fe Tranmentioning
confidence: 99%
See 2 more Smart Citations